Critique of Theodicy of Soul Cultivation of John Hick based on Verses from the Holy Quran - Masoumeh RajabNezhadian, Abdullah HosseiniEskandian (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
John Hick Theodicy, in which he was most influenced by Irenaeus, seeks to prove divine justice and dispel human skepticism about the evils of the universe.In this theodicy, John Hick considers the problem of evil, which in modern times has led to many doubts among the theologians, to be perfectly compatible with the existence of a benevolent and wise God but in the meantime, he considered some of the existing evils to be exaggerated and useless, and that this issue and a few other details of Hick's thought mentioned in his Theodicy did not correspond to the teachings of the Holy Quran.Therefore, examining the theodicy of soul cultivation of John Hick and comparing it with the verses of the Holy Quran and also criticizing it according to the teachings of the Holy Qur'an can help us to understand the reason for the occurrence of evil in the good system and the weaknesses of the theodicy of John Hick.In this descriptive-analytical research, first the information about the theodicy of soul cultivation is presented, then the subject is continued by defining and expressing the nature of evil and the types of evil from John Hick's point of view, and finally, the issue ends with a critique of the theology of soul cultivation according to the verses of the Holy Quran.In his theodicy, John Hick, while considering evil as a necessity of a good system, has presented ideas contrary to reason and the Qur'an, and has considered some evil as infinite, and believes that man commits sin due to his epistemological distance from God, while the Holy Quran rejects such beliefs.